2020
DOI: 10.3390/v12101179
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Copper Ions Differentially Regulate Prion-Like Phase Separation Dynamics of Pan-Virus Nucleocapsid Biomolecular Condensates

Abstract: Liquid-liquid phase separation (LLPS) is a rapidly growing research focus due to numerous demonstrations that many cellular proteins phase-separate to form biomolecular condensates (BMCs) that nucleate membraneless organelles (MLOs). A growing repertoire of mechanisms supporting BMC formation, composition, dynamics, and functions are becoming elucidated. BMCs are now appreciated as required for several steps of gene regulation, while their deregulation promotes pathological aggregates, such as stress granules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 330 publications
(427 reference statements)
2
19
0
Order By: Relevance
“…Again, a role for structural disorder and protein multivalence has been hypothesized, since the NC ZnF overlaps with a prion-like domain (PLD), which is conserved in other retroviral Gag proteins capable of undergoing LLPS [199]. As already mentioned above, evidence of PLD-driven LLPS has long been recognized in proteins involved in neurodegeneration, with a possible mechanistic link between coacervate formation and amyloid fibrillation [121].…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
“…Again, a role for structural disorder and protein multivalence has been hypothesized, since the NC ZnF overlaps with a prion-like domain (PLD), which is conserved in other retroviral Gag proteins capable of undergoing LLPS [199]. As already mentioned above, evidence of PLD-driven LLPS has long been recognized in proteins involved in neurodegeneration, with a possible mechanistic link between coacervate formation and amyloid fibrillation [121].…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
“…NC contains two highly conserved ZnF domains responsible for many functions essential for the replication of the virus including binding nucleic acids (single-stranded DNA and RNA), as well as condensing and annealing them [209]. It was recently shown that in in vitro assays, NC as well as the uncleaved Gag can undergo LLPS, forming liquid structures that are spherical, divide, fuse, and the process is governed by the ZnF domain of NC [210]. It is accepted that proteins that undergo LLPS typically contain IDR or LCD and can bind DNA and RNA scaffolds through ZnFs or RNA-recognition motifs [85].…”
Section: Assembly and Budding Of Hivmentioning
confidence: 99%
“…Distinctly, the IB scaffolds of NNS RNA viruses, nucleoproteins and/or phosphoproteins, contain a high content of IDRs [ 109 ]. Recent bioinformatics analyses of viral proteins further revealed that many of the viral IDRs are prion-like disordered domains (PrLD) [ 110 ]. PrLDs are intimately linked to many neurodegenerative diseases because they are prone to misfold and form insoluble solid-like protein aggregates via aberrant phase transition [ 111 ].…”
Section: Perspectivesmentioning
confidence: 99%